Analysis of coffee farming in Sukorambi sub-district, Jember district - Ibrahim, Villa Akbar; Widjayanti , Fefi Nurdiana; Prayuginingsih , Henik (International Applied Science, 2023)
Coffee is one of the plantation commodities which has quite an important role in economic activities in Indonesia. The types of coffee that are widely cultivated in Jember Regency are robusta and arabica coffee. The aim of this research is to identify: (1) the benefits of coffee farming (2) the cost efficiency of coffee farming in Sukorambi District, Jember Regency. The method used is a descriptive analytical method with a survey approach with a total of 52 farmers as respondents. Sampling used total sampling and snowball sampling . Data analysis uses descriptive analysis. The research results show that: (1) coffee farming is profitable, amounting to Rp. 5,624,180/ha. (2) the use of costs in coffee farming is efficient with an R/C value of 1.05